Black semitransparent antistatic polyurethane optical film and preparation method thereof

By using a simple physical sand grinding process of black composite color paste and water-based polyurethane, the problems of complex and single function of existing polyurethane optical films were solved, and black translucent polyurethane optical with high color depth, optical transparency and antistatic properties were prepared. Thin film, achieving environmentally friendly and high-performance film preparation.

CN119192820APending Publication Date: 2024-12-27CHANGZHOU XIYAO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411297270.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing polyurethane optical films have complex processes and cumbersome processes, involving chemical modification of graphene and polyurethane, and use toxic solvents. The product functions are single, poor versatility, and there is an uneven black spot problem when the thin coating film is transparent.

Method used

Using black composite color paste, including graphene aqueous dispersion, carbon black slurry and dispersant, uniform composite color paste is prepared by stirring and sand milling, combined with aqueous polyurethane, simple physical sand grinding or blending process is carried out to prepare Black translucent antistatic polyurethane optical film avoids chemical synthesis and the use of organic solvents.

Benefits of technology

It improves the color depth, optical transparency and antistatic properties of the film, enhances overall performance and stability, is suitable for thin-coated products, is environmentally friendly, and does not require organic reagents.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane optical films, in particular to a black semitransparent antistatic polyurethane optical film and a preparation method thereof. The invention relates to a black semitransparent antistatic polyurethane optical film, which comprises the following substances by weight: 8-32 parts of black composite color paste; 85 to 150 parts of waterborne polyurethane; the solid content of the black composite color paste is 5-8%. The black composite color paste is added, so that the color depth of the film can be enhanced, the optical transparency of the film can be improved, the visual effect of the film can reach a semitransparent state, meanwhile, the solid content of the black composite color paste is optimized, and proper color paste materials are selected; according to the preparation method, the black composite color paste is added into the polyurethane optical film, so that the light transmittance of the film is adjusted, the polyurethane optical film with proper blackness is prepared, and meanwhile, graphene is added into the black composite color paste, so that the mechanical property of the polyurethane optical film is further improved while the antistatic property of the polyurethane film is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane optical films, in particular to a black semi-transparent antistatic polyurethane optical film and a preparation method thereof. Background Art

[0002] LED protective film is to protect the screen surface of the product from pollution and damage from the external environment, and it can also filter light, thereby extending the life of the screen. Common protective films include acrylic protective film and silicone protective film, while polyurethane protective film is another emerging product in recent years. Polyurethane protective film is a functional protective film made of transparent PET as the substrate, coated with polyurethane glue on one side, and a release film on the back. It is then transferred to the screen surface of electronic products by high-temperature heat transfer. It is mainly used to protect products such as LCD panels, ITO and glass panels. The advantages of polyurethane protective film are quite obvious. Its process is simple, the price is lower than that of products such as silicone, and it can solve problems such as bubbles and fogging. At the same time, polyurethane film is scratch-resistant, high temperature and high humidity, and has a long service life.

[0003] In the prior art Chinese patent CN117210160A, the inventor disclosed a graphene-based antistatic polyurethane protective film and a preparation method thereof. The protective film uses the properties of graphene to give the polyurethane film an antistatic effect.

[0004] In view of the above-mentioned related technologies, the inventors found that the existing polyurethane optical film process route is complicated and the process is cumbersome. It involves the chemical modification of graphene and the chemical modification of polyurethane. The process is complicated and environmentally friendly. A large amount of organic solvents, such as trifluoroacetic acid, dichloromethane and other toxic reagents, are used in the experiment. At the same time, the final product has a single function. In addition to the protection brought by the polyurethane itself, there is only the antistatic effect brought by graphene and antistatic agents. At the same time, the modified graphene in the invention is only effective for the polyurethane synthesized in the invention, and its versatility is poor. At the same time, in the case of thick coating, the dispersion defects of the pigment in the polyurethane will be covered up. In the case of thin coating (that is, the thickness of the final product is less than 3μm), the polyurethane film will be transparent. At this time, the dispersion defects of inorganic pigments such as graphene will be magnified, and the naked eye will find that there are a large number of uneven black spots on the surface of the film. Summary of the invention

[0005] In order to improve the above technical problems, the present application provides a black translucent antistatic polyurethane optical film and a preparation method thereof.

[0006] A black translucent antistatic polyurethane optical film adopts the following technical solution: A black translucent antistatic polyurethane optical film comprises the following materials in parts by weight: Black composite color paste 8-32 parts; 85-150 parts of waterborne polyurethane; The solid content of the black composite color paste is 5-8%.

[0007] Through the above technical scheme, the addition of the black composite colorant selected in this application can not only enhance the color depth of the film, but also improve its optical transparency, making it visually translucent. At the same time, by optimizing the solid content of the black composite colorant and selecting suitable colorant materials, the transmittance of the film can be adjusted while preparing a polyurethane optical film with appropriate blackness.

[0008] Furthermore, the black composite color paste includes the following materials in parts by weight: 45-55 parts of graphene aqueous dispersion; Dispersant 0.5-2.0 parts; 8-15 parts of carbon black paste; 35-45 parts of deionized water.

[0009] Through the above technical solution, the present application selects to compound graphene and carbon black paste and use them together as black pigments of polyurethane. At the same time, the addition of graphene can also reduce the surface resistivity of polyurethane film and give the film antistatic effect. At the same time, the present application optimizes the components in the black composite color paste and adds a dispersant to ensure the uniform dispersion of the composite color paste during the preparation process, avoid the occurrence of particle aggregation, and thus improve the overall performance and stability of the film.

[0010] Furthermore, the graphene aqueous dispersion is prepared by the following scheme: Mix the dispersant with deionized water, disperse and stir to obtain a dispersed mixed liquid; The graphene powder is added to the dispersed mixed liquid, mixed and stirred, and then sand-milled to control the particle size D50 of the dispersed liquid to 0.5±0.1 μm. The graphene aqueous dispersion can be collected by stopping the ball milling.

[0011] Furthermore, the stirring rate of the dispersion stirring process is 400-600 rpm.

[0012] Furthermore, the stirring rate of the mixing and stirring process is 800-1200 rpm, and the rotation speed of the sand grinding process is 2200-2800 rpm.

[0013] Through the above technical scheme, the present application optimizes the preparation process parameters, and the mixing of the dispersant and water can be effectively promoted by a stirring rate of 400-600rpm, thereby improving the dispersibility and stability of graphene. This process ensures the uniformity and stability of the dispersion, laying the foundation for subsequent mixing and sand milling. On this basis, the present application adjusts the rate settings of the mixing and stirring treatment and the sand milling treatment to ensure the uniform mixing of the black composite color paste and the full dispersion of graphene, respectively. High-speed stirring can effectively break up the aggregated particles, so that the various components in the color paste are evenly distributed and its performance is improved. At the same time, the high speed of the sand milling treatment can further reduce the particle size, optimize the fluidity and stability of the dispersion, and ensure the excellent optical and electrical performance of the final film.

[0014] In a second aspect, the present application provides a method for preparing a black translucent antistatic polyurethane optical film, using the following technical solution: A method for preparing a black translucent antistatic polyurethane optical film comprises the following preparation steps: Preparation of black composite color paste: After mixing the graphene aqueous dispersion with the carbon black slurry, a dispersant is added and stirred for dispersion treatment, and a black composite color paste is collected; Preparation of modified polyurethane dispersion: black composite color paste and waterborne polyurethane are stirred and mixed and allowed to stand for degassing to obtain modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Take the modified polyurethane dispersion and apply it to the surface of the substrate. After the coating is completed, it is dried in an oven to prepare the modified polyurethane thin coating.

[0015] Through the above technical scheme, the present application systematically designs the mixing steps of the black composite color paste and the waterborne polyurethane, ensuring the stability and performance of the final product. Through a simple physical sanding or blending process, no complex steps such as chemical synthesis are involved. At the same time, no organic reagents are used in the process, and the overall environmental friendliness is high. The whole process is completed in the water phase. In terms of performance, the graphene carbon black composite color paste prepared in the present invention has stronger coloring ability and is more suitable for the preparation process of thin-coated products. It can give the film (thickness less than 3μm) a black and translucent effect.

[0016] Furthermore, the thickness of the modified polyurethane thin coating film is not higher than 3 μm.

[0017] Furthermore, the dispersant includes at least one of sodium carboxymethyl cellulose, BYK2013, BYK190 and BASF 4560.

[0018] Furthermore, the total dry weight of graphene and carbon black in the modified polyurethane dispersion accounts for 2-8% of the dry weight of the waterborne polyurethane.

[0019] Through the above technical solution, the present application adjusts the ratio of the total dry weight of graphene and carbon black to the dry weight of waterborne polyurethane, ensuring that the film maintains appropriate light transmittance while having good mechanical strength and antistatic properties.

[0020] In summary, this application has the following beneficial effects: First, the addition of the black composite color paste selected in this application can not only enhance the color depth of the film, but also improve its optical transparency, making it visually translucent. At the same time, by optimizing the solid content of the black composite color paste and selecting appropriate color paste materials, the light transmittance of the film can be adjusted while preparing a polyurethane optical film with appropriate blackness.

[0021] Second, the present application selects to compound graphene and carbon black paste and use them together as black pigments for polyurethane. At the same time, the addition of graphene can also reduce the surface resistivity of the polyurethane film and give the film an antistatic effect. At the same time, the present application optimizes the components in the black composite color paste and adds a dispersant to ensure the uniform dispersion of the composite color paste during the preparation process, avoiding the occurrence of particle aggregation, thereby improving the overall performance and stability of the film.

[0022] Third, the present application systematically designs the mixing steps of the black composite color paste and waterborne polyurethane to ensure the stability and performance of the final product. It uses a simple physical sanding or blending process without involving complex steps such as chemical synthesis. At the same time, no organic reagents are used in the process, and the overall environmental friendliness is high. The entire process is completed in the water phase. In terms of performance, the graphene carbon black composite color paste prepared in the present invention has stronger coloring ability and is more suitable for the preparation process of thin-coated products. It can give the film (thickness less than 3μm) a black and translucent effect. DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments.

[0024] In the examples of the present application, the raw materials and instruments used are as follows, but not limited thereto: The graphene powder is selected from HG-G conductive graphene powder of Hebei Huage Graphene Materials Co., Ltd. and SE1231 graphene of Changzhou Sixth Element Materials Technology Co., Ltd. The material selected in the embodiment of the present application is HG-G graphene; Dispersant for graphene: sodium carboxymethyl cellulose CMC, BYK2013, BYK190, BASF 4560. In the embodiment of the present application, CMC is selected as the dispersant for graphene powder; High-pigment carbon black paste: S803 color paste from Shenzhen Tyco Technology Co., Ltd., Y3918X color paste from Anyang Wangtai New Materials Co., Ltd., and PN9006 nano color paste from Jiangxi Mitsukoshi New Materials Co., Ltd. In the present application example, S803 color paste is selected, and its effective solid content of carbon black is 30%.

[0025] Water-based polyurethane: Anhui Dawei Huatai New Materials Co., Ltd.'s F1502 model water-based polyurethane has an effective solid content of 30%.

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] Preparation Example 1 Preparation of graphene aqueous dispersion: According to the solid content of the dispersant being 1%, the dispersant is mixed with deionized water, and dispersed and stirred evenly using a high-speed disperser at a speed of 400 rpm for 20 min. After stirring evenly, the dispersed mixed liquid is collected; Then, according to the solid content of graphene being 6%, the graphene powder is added to the dispersed mixed liquid, and after stirring and mixing at a rotation speed of 800 rpm for 20 minutes, it is placed in a sand mill and then sand-milled at a rotation speed of 2200 rpm and a zirconium bead size of 0.4-0.6 mm. Samples are taken every 30 minutes to test the particle size. When the particle size D50 of the graphene aqueous dispersion is 0.5±0.1 μm, the ball milling is stopped to collect the graphene aqueous dispersion 1.

[0028] Preparation Example 2 Preparation of graphene aqueous dispersion: According to the solid content of the dispersant being 1%, the dispersant is mixed with deionized water, and dispersed and stirred evenly using a high-speed disperser at a speed of 500 rpm for 20 minutes. After stirring evenly, the dispersed mixed liquid is collected; Then, according to the solid content of graphene being 6%, the graphene powder is added to the dispersed mixed liquid, and after stirring and mixing at a rotation speed of 1000 rpm for 20 minutes, it is placed in a sand mill and then sand-milled at a rotation speed of 2500 rpm and a zirconium bead size of 0.4-0.6 mm. Samples are taken every 30 minutes to test the particle size. When the particle size D50 of the graphene aqueous dispersion is 0.5±0.1 μm, the ball milling is stopped to collect the graphene aqueous dispersion 2.

[0029] Preparation Example 3 Preparation of graphene aqueous dispersion: According to the solid content of the dispersant being 1%, the dispersant is mixed with deionized water, and dispersed and stirred evenly using a high-speed disperser at a speed of 600 rpm for 20 min. After stirring evenly, the dispersed mixed liquid is collected; Then, according to the solid content of graphene being 6%, the graphene powder is added to the dispersed mixed liquid, and after stirring and mixing at a rotation speed of 1200 rpm for 20 minutes, it is placed in a sand mill and then sand-milled at a rotation speed of 2800 rpm and a zirconium bead size of 0.4-0.6 mm. Samples are taken every 30 minutes to test the particle size. When the particle size D50 of the graphene aqueous dispersion is 0.5±0.1 μm, the ball milling is stopped to collect the graphene aqueous dispersion 3.

[0030] Example 1 Preparation of black composite color paste: After mixing 45 g of graphene aqueous dispersion 1 with 8 g of carbon black slurry, 0.5 g of dispersant CMC was added, and the mixture was stirred at 1000 rpm for 1 h to obtain a black composite color paste with a graphene solid content of 3% and a carbon black solid content of 3%; Preparation of modified polyurethane dispersion: based on the total weight of graphene carbon black accounting for 2% of the dry weight of polyurethane, 2g of black composite color paste and 20g of waterborne polyurethane were stirred at 1000rpm for 30min, and then allowed to stand for degassing for 1h to collect the modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Use a 20 μm wire rod to coat the modified polyurethane dispersion on the PET substrate, and dry it in an 80°C oven for 10 seconds, then take it out to obtain the graphene / carbon black modified polyurethane protective film.

[0031] Example 2 Preparation of black composite color paste: After mixing 50g of graphene aqueous dispersion 2 with 15g of carbon black slurry, 2g of dispersant CMC was added, and the mixture was stirred at 1000rpm for 1h to obtain a black composite color paste with a graphene solid content of 3% and a carbon black solid content of 3%; Preparation of modified polyurethane dispersion: based on the total weight of graphene carbon black accounting for 2% of the dry weight of polyurethane, 2g of black composite color paste and 20g of waterborne polyurethane were stirred at 1000rpm for 30min, and then allowed to stand for degassing for 1h to collect the modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Use a 20 μm wire rod to coat the modified polyurethane dispersion on the PET substrate, and dry it in an 80°C oven for 10 seconds, then take it out to obtain the graphene / carbon black modified polyurethane protective film.

[0032] Example 3 Preparation of black composite color paste: After mixing 55 g of graphene aqueous dispersion 3 with 10 g of carbon black slurry, 1 g of dispersant CMC was added, and the mixture was stirred at 1000 rpm for 1 h to obtain a black composite color paste with a graphene solid content of 3% and a carbon black solid content of 3%; Preparation of modified polyurethane dispersion: based on the total weight of graphene carbon black accounting for 2% of the dry weight of polyurethane, 2g of black composite color paste and 20g of waterborne polyurethane were stirred at 1000rpm for 30min, and then allowed to stand for degassing for 1h to collect the modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Use a 20 μm wire rod to coat the modified polyurethane dispersion on the PET substrate, and dry it in an 80°C oven for 10 seconds, then take it out to obtain the graphene / carbon black modified polyurethane protective film.

[0033] Example 4 Preparation of black composite color paste: After mixing 50 g of graphene aqueous dispersion 1 with 15 g of carbon black slurry, 2 g of dispersant CMC was added, and the mixture was stirred at 1000 rpm for 1 h to obtain a black composite color paste with a graphene solid content of 3% and a carbon black solid content of 3%; Preparation of modified polyurethane dispersion: based on the total weight of graphene carbon black accounting for 3% of the dry weight of polyurethane, 3g of black composite color paste and 20g of waterborne polyurethane were stirred at 1000rpm for 30min, and then allowed to stand for degassing for 1h to obtain the modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Use a 20 μm wire rod to coat the modified polyurethane dispersion on the PET substrate, and dry it in an 80°C oven for 10 seconds, then take it out to obtain the graphene / carbon black modified polyurethane protective film.

[0034] Example 5 Preparation of black composite color paste: After mixing 50 g of graphene aqueous dispersion 1 with 15 g of carbon black slurry, 2 g of dispersant CMC was added, and the mixture was stirred at 1000 rpm for 1 h to obtain a black composite color paste with a graphene solid content of 3% and a carbon black solid content of 3%; Preparation of modified polyurethane dispersion: based on the total weight of graphene carbon black accounting for 4% of the dry weight of polyurethane, 4g of black composite color paste and 20g of waterborne polyurethane were stirred at 1000rpm for 30min, and then allowed to stand for degassing for 1h to obtain the modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Use a 20 μm wire rod to coat the modified polyurethane dispersion on the PET substrate, and dry it in an 80°C oven for 10 seconds, then take it out to obtain the graphene / carbon black modified polyurethane protective film.

[0035] Example 6 Preparation of black composite color paste: After mixing 50 g of graphene aqueous dispersion 1 with 15 g of carbon black slurry, 2 g of dispersant CMC was added, and the mixture was stirred at 1000 rpm for 1 h to obtain a black composite color paste with a graphene solid content of 3% and a carbon black solid content of 3%; Preparation of modified polyurethane dispersion: based on the total weight of graphene carbon black accounting for 6% of the dry weight of polyurethane, 6g of black composite color paste and 20g of waterborne polyurethane were stirred at 1000rpm for 30min, and then allowed to stand for degassing for 1h to obtain the modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Use a 20 μm wire rod to coat the modified polyurethane dispersion on the PET substrate, and dry it in an 80°C oven for 10 seconds, then take it out to obtain the graphene / carbon black modified polyurethane protective film.

[0036] Example 7 Preparation of black composite color paste: After mixing 50 g of graphene aqueous dispersion 1 with 15 g of carbon black slurry, 2 g of dispersant CMC was added, and the mixture was stirred at 1000 rpm for 1 h to obtain a black composite color paste with a graphene solid content of 3% and a carbon black solid content of 3%; Preparation of modified polyurethane dispersion: based on the total weight of graphene carbon black accounting for 8% of the dry weight of polyurethane, 8g of black composite color paste and 20g of waterborne polyurethane were stirred at 1000rpm for 30min, and then allowed to stand for degassing for 1h to obtain the modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Use a 20 μm wire rod to coat the modified polyurethane dispersion on the PET substrate, and dry it in an 80°C oven for 10 seconds, then take it out to obtain the graphene / carbon black modified polyurethane protective film.

[0037] Comparative Example 1 The preparation method of the polyurethane protective film in this embodiment is the same as that in Embodiment 1, except that the addition amount of the graphene aqueous dispersion 1 is 31.5 g, that is, the graphene accounts for 9% of the dry weight of the polyurethane.

[0038] Comparative Example 2 The preparation method of the polyurethane protective film in this embodiment is the same as that in Example 1, except that the black composite color paste is adjusted to 4 g and the addition amount of the graphene aqueous dispersion 1 is 4 g, that is, the graphene accounts for 4% of the dry weight of the polyurethane.

[0039] Comparative Example 3 The preparation method of the modified polyurethane protective film in this comparative example is the same as that in Example 1. The difference is that in this comparative example, no graphene is added, and only carbon black slurry is added. First, the S803 carbon black slurry is diluted to obtain a color slurry with a solid content of 6%, and then 4g of the diluted color slurry is mixed with the water-based polyurethane, that is, the weight of carbon black accounts for 4% of the dry weight of the polyurethane.

[0040] Performance Testing The performance of the polyurethane protective films prepared in Examples 1-7 and Comparative Examples 1-3 was tested: Light transmittance: Use WH-100 model haze meter to test the light transmittance of modified polyurethane protective film; Blackness: Blackness = 1-transmittance; Surface resistance: Use a surface resistance meter to measure the resistivity of the polyurethane film surface.

[0041] The details are shown in Table 1 below: Table 1 Performance test table project Transmittance / % Blackness / % Surface resistance / Ω Example 1 56.1 43.9 — Example 2 56.3 43.7 — Example 3 56.0 47.0 — Example 4 41.8 58.2 — Example 5 32.6 67.4 <![CDATA[10 11 ]]> Example 6 17.9 82.1 <![CDATA[10 8 ]]> Example 7 5.5 94.5 <![CDATA[10 5 ]]> Comparative Example 1 91.5 — — Comparative Example 2 34.5 65.5 <![CDATA[10 5 ]]> Comparative Example 3 29.4 70.6 — It should be noted that in the present invention, graphene mainly plays an antistatic effect, and carbon black slurry mainly plays a coloring effect. In the technical solution of the present application, the ratio of graphene carbon black composite slurry is fixed, so in the final result, the transmittance, blackness and surface results are consistent. For example, the increase in the amount of total pigment added leads to low transmittance, high blackness and low surface resistance. However, in the actual application process, according to customer needs, by adjusting the ratio of graphene and carbon black in the composite color paste, the blackness and surface resistance can be regulated. For example, increasing the amount of graphene added can make the surface resistance value lower and the antistatic effect better when the blackness is low and the transmittance is high. Or increase the amount of carbon black slurry added so that the film has a high surface resistance when the blackness is high.

[0042] From the results of the above Examples 1-7, Comparative Examples 1-3 and Table 1, it can be found that: As the amount of graphene-carbon black slurry added increases, the transmittance of the final modified polyurethane film is significantly reduced, while the blackness is significantly increased. This shows that in the present invention, the transmittance of the polyurethane protective film, that is, the light filtering effect, can be adjusted according to actual needs, so it will have a wide range of applications in optical protection.

[0043] Secondly, with the increase of graphene addition, the surface resistance of the modified polyurethane film is greatly reduced. When the addition amount of graphene reaches 2%, the polyurethane film already has a certain antistatic effect. When the addition amount reaches 4%, the surface resistance of the polyurethane film can reach the conductive range.

[0044] From Comparative Examples 2 and 3, it can be seen that at the same addition amount, the coloring ability of carbon black is stronger than that of graphene, but when the carbon black slurry is thinly coated, there are a large number of black spots on the surface. This is because the compatibility of carbon black slurry in waterborne polyurethane is not as good as expected. When the film thickness is large, no defects can be seen, but when the polyurethane film thickness is small, this shortcoming will be magnified. Graphene does not have this problem. Therefore, in the present invention, it is decided to use the two together as a colorant and antistatic agent for polyurethane.

[0045] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0046] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0047] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0048] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A black translucent antistatic polyurethane optical film, characterized in that: The composition includes the following materials in parts by weight: Black composite color paste 8-32 parts; 85-150 parts of waterborne polyurethane; The solid content of the black composite color paste is 5-8%.

2. The black translucent antistatic polyurethane optical film according to claim 1, characterized in that: The black composite color paste comprises the following materials in parts by weight: 45-55 parts of graphene aqueous dispersion; Dispersant 0.5-2.0 parts; 8-15 parts of carbon black paste; 35-45 parts of deionized water.

3. The black translucent antistatic polyurethane optical film according to claim 1, characterized in that: The graphene aqueous dispersion is prepared by the following scheme: Mix the dispersant with deionized water, disperse and stir to obtain a dispersed mixed liquid; The graphene powder is added to the dispersed mixed liquid, mixed and stirred, and then sand-milled to control the particle size D50 of the dispersed liquid to 0.5±0.1 μm. The graphene aqueous dispersion can be collected by stopping the ball milling.

4. The black translucent antistatic polyurethane optical film according to claim 3, characterized in that: The stirring rate of the dispersion stirring process is 400-600 rpm.

5. The black translucent antistatic polyurethane optical film according to claim 3, characterized in that: The stirring rate of the mixing and stirring process is 800-1200 rpm, and the rotation speed of the sand grinding process is 2200-2800 rpm.

6. A method for preparing a black translucent antistatic polyurethane optical film according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: Preparation of black composite color paste: After mixing the graphene aqueous dispersion with the carbon black slurry, a dispersant is added and stirred for dispersion treatment, and a black composite color paste is collected; Preparation of modified polyurethane dispersion: black composite color paste and waterborne polyurethane are stirred and mixed and allowed to stand for degassing to obtain modified polyurethane dispersion; Preparation of modified polyurethane thin coating: Take the modified polyurethane dispersion and apply it to the surface of the substrate. After the coating is completed, it is dried in an oven to prepare the modified polyurethane thin coating.

7. The method for preparing a black translucent antistatic polyurethane optical film according to claim 4, characterized in that: The modified polyurethane thin coating film has a thickness of no greater than 3 μm.

8. The method for preparing a black translucent antistatic polyurethane optical film according to claim 4, characterized in that: The dispersant includes at least one of sodium carboxymethyl cellulose, BYK2013, BYK190 and BASF 4560.

9. The method for preparing a black translucent antistatic polyurethane optical film according to claim 4, characterized in that: The total dry weight of graphene and carbon black in the modified polyurethane dispersion accounts for 2-8% of the dry weight of the waterborne polyurethane.

Citation Information

Cited By

  • Black optical protective film for COB display screen and preparation method and application thereof

    CN121825437A